Controlling factors of benthic macroinvertebrates distribution in a small tropical pond, lateral to the Paranapanema River (São Paulo, Brazil). - Shimabukuro, Erika Mayumi; Henry, Raoul (My University, 2011)
The aim of the present study was to examine the benthic fauna in a marginal pond lateral to the Paranapanema River and to identify the main controlling factors of its distribution. Considering the small size of the lacustrine ecosystem, we expected that seasonal variations of the benthic community attributes are more important than spatial variations; Methods: Two samplings, one in March and another in August, were carried out at nine sites in the pond. Sediment samples were obtained through a Van Veen grab for invertebrate sorting, granulometric analysis, and for quantification of organic matter in sediment. Other abiotic factors were measured, such as water transparency, dissolved oxygen, pH, electric conductivity, temperature, and depth of sediment sampling sites. Regarding the comparative analysis at spatial scale, no significant variations in density of the benthic invertebrate community were found. Results: In relation to the studied abiotic factors, only depth presented significant differences among sampling sites; All the measured environmental parameters presented significant differences among sampling months, except depth and the physical and chemical characteristics of the sediment. The abundance of Chaoboridae and Chironomidae was the unique attribute with a significant difference in comparing the two months. A higher abundance of taxa occurred in August, especially for Oligochaeta, Nematoda, Chaoboridae, and Chironomidae; Conclusions: Because of the low structural complexity of the studied pond, we concluded that the changes in benthic macroinvertebrate community attributes were mainly due to seasonal effects.

Objetivo: O presente estudo tem por objetivo examinar a fauna bentônica em lagoa marginal ao rio Paranapanema e os principais fatores reguladores da sua distribuição. Devido ao pequeno tamanho do ambiente lacustre, procurou-se mostrar que as variações sazonais dos atributos da comunidade bentônica são mais importantes do que as variações espaciais; Métodos: Duas coletas, uma em março e outra em agosto foram realizadas, em nove locais na lagoa. Amostras de sedimento foram obtidas com um pegador de Van Veen, para análise dos invertebrados, da granulometria e da quantidade de matéria orgânica do sedimento. Outros fatores abióticos foram medidos, como a transparência, o oxigênio dissolvido, o pH, a condutividade elétrica, a temperatura da água e a profundidade do local de amostragem do sedimento; Resultados: Na análise comparativa no nível de escala espacial, não houve variações significativas na densidade da comunidade de invertebrados bentônicos. Com relação aos fatores abióticos estudados, apenas a profundidade apresentou diferença significativa entre os pontos de amostragem. Todos os parâmetros ambientais mensurados, exceto a profundidade e as características físico-químicas do sedimento, apresentaram diferença significativa entre os meses de estudo. A abundância dos táxons Chaoboridae e Chironomidae foi o único atributo a apresentar diferença significativa entre os meses. Chaoboridae foi dominante em março e Chironomidae mais abundante em agosto. Maior abundância de táxons ocorreu em agosto, com destaque para os grupos Oligochaeta, Nematoda, Chaoboridae e Chironomidae; Conclusões: Em função da baixa complexidade estrutural da lagoa estudada, concluiu-se que a comunidade de macroinvertebrados bentônicos é alterada mais expressivamente em razão da sazonalidade, sofrendo menos influência de modificações espaciais.
Macroinvertebrados bentônicos e fatores controladores de sua distribuição em uma pequena lagoa tropical adjacente ao rio Paranapanema (São Paulo, Brasil)